KORELASI ANTARA PENEBALAN TUNIKA INTIMA-MEDIA ARTERI KAROTIS KOMUNIS DENGAN LUAS INFARK PADA STROKE ISKEMIK - , Mujiyono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Ischemic stroke is one of the leading causes of death in adults, and the incidence is increase every year. Ischemic stroke is caused by blockage of serebroservikal arterywith thrombus or embolism. Thrombus is complication of atherosclerosis process. Stroke ischemic largely due to thrombus.Carotid intima-media thickness (IMT) is a predictor of incident ischemic stroke. There is an increased incidence of stroke with increased carotid IMT. Objective: To determine the correlation between intima-media thickening of the carotid artery with wideof infarct in ischemic stroke. Materials and methods : This study is an observational analytic study with cross sectional design. The study subjects consisted of ischemic stroke group and no stroke group, each consisting of 35 subjects.Measuring instruments used were questionnaires and B-mode ultrasound examination. Patients, by consecutive sampling, were examined IMT of the common carotid artery at the right and left side. Ultrasound examination using GE Logic P3 with a frequency of 8 MHz linear transducer, carotid programs, depth 4 cm and 2 times zoom, on the far wall in six different places. The greatest value of the right and left mean IMT is used as a figure IMT. In ischemic stroke group patients,it carried out a review of the CT scan images, determined the infarctlocation, and calculation the width of infarcts. Correlation between variables was assessed using Pearson correlation analysis. Results: The correlation between IMT with wide of infarct: r= 0.46, p= 0.8. The mean IMT in the ischemic stroke group is 1.2 ± 0.05, whereas in the non-stroke group is 0.07 ± 0.01 (p value = 0.00) In the ischemic stroke group, the mean right-side IMT is 0.11 ± 0.05, and mean left-side IMT is 0.10 ± 0.04 (p value = 0.00). In the non-stroke group, the mean right-side IMT is 0.6 ± 0.2, and the mean left-side IMT is 0.7 ± 0.1 (p value = 0.21). Conclusion: There is no significant correlation between intima-media thickness of common carotid artery with wideof infarct in ischemic stroke patients. There is a significant difference between the mean IMT in ischemic stroke patients compared with the non-stroke patients